Eliciting the Level of Health Inequality Aversion in England. (20th September 2016) - Robson, Matthew; Asaria, Miqdad; Cookson, Richard; Tsuchiya, Aki; Ali, Shehzad
Abstract: Health inequality aversion parameters can be used to represent alternative value judgements about policy concern for reducing health inequality versus improving total health. In this study, we use data from an online survey of the general public in England ( n = 244) to elicit health inequality aversion parameters for both Atkinson and Kolm social welfare functions. We find median inequality aversion parameters of 10.95 for Atkinson and 0.15 for Kolm. These values suggest substantial concern for health inequality among the English general public which, at current levels of quality adjusted life expectancy, implies weighting health gains to the poorest fifth of people in society six to seven times as highly as health gains to the richest fifth. © 2016 The Authors. Health Economics published by John Wiley & Sons, Ltd.